2009
DOI: 10.1039/b900960d
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of hydroxyl radicals with neonicotinoid insecticides: mechanism and changes in toxicity

Abstract: The reactivity of hydroxyl radicals (HO ) towards three neonicotonoid insecticides, namely imidacloprid, thiacloprid and acetamiprid was investigated. These radicals were generated by photolysis of H(2)O(2) solutions. Flash photolysis experiments were used to determine the rate constants of 5.5 x 10(10) M(-1)s(-1), 6 x 10(10) M(-1)s(-1), and 7.5 x 10(10) M(-1)s(-1), for the reactions of HO with acetamiprid, imidacloprid, and thiacloprid, respectively. Continuous irradiation experiments in the absence and prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
39
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 31 publications
10
39
1
7
Order By: Relevance
“…Photocatalytic treatment of the mixture led to 60% removal of acetamiprid with a Q UV of 5.5 kJ L and was negligible when 0.01 mol L −1 2‐propanol was present, indicating that HO · , which reacts with acetamiprid with a rate constant of k HO· = 5 × 10 10 M −1 s −1 , is probably the main species involved in the photocatalytic degradation of the pesticide, as proposed by Guzsvany et al Surprisingly, when the photocatalytic treatment was applied in the absence of the other two pesticides, the removal of acetamiprid was lower (40% for the same Q UV ), which could indicate that intermediates and/or reactive species generated during the degradation of the other two pesticides exert a positive effect on the elimination of acetamiprid. Figure shows that during the first kJ L −1 , the evolution of acetamiprid over Q UV was practically the same regardless of the presence of the other pesticides, which coincides with the accumulated UV energy needed for total disappearance of both thiabendazole (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Photocatalytic treatment of the mixture led to 60% removal of acetamiprid with a Q UV of 5.5 kJ L and was negligible when 0.01 mol L −1 2‐propanol was present, indicating that HO · , which reacts with acetamiprid with a rate constant of k HO· = 5 × 10 10 M −1 s −1 , is probably the main species involved in the photocatalytic degradation of the pesticide, as proposed by Guzsvany et al Surprisingly, when the photocatalytic treatment was applied in the absence of the other two pesticides, the removal of acetamiprid was lower (40% for the same Q UV ), which could indicate that intermediates and/or reactive species generated during the degradation of the other two pesticides exert a positive effect on the elimination of acetamiprid. Figure shows that during the first kJ L −1 , the evolution of acetamiprid over Q UV was practically the same regardless of the presence of the other pesticides, which coincides with the accumulated UV energy needed for total disappearance of both thiabendazole (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Direct photolysis has also been observed, with large variations in quantum yield between neonicotinoids and half‐lives ranging from 12 min for imidacloprid to 42 h for thiacloprid (Lu et al ). Indirect photolysis has been studied, with half‐life estimates of 5 h to 19 d in aquatic reservoirs, indicating that hydroxyl radicals may play a role in neonicotinoid photolysis (Dell'Arciprete et al ). The comparison of direct and indirect photolysis in the same study, however, has not been reported, and updated actinometry values (Laszakovits et al ) require validation of previously reported quantum yields.…”
Section: Introductionmentioning
confidence: 99%
“…According to the article, 19 6-chloronicotinic acid (6-CNA) is regarded as the degradation product of ACT by photocatalytic oxidation. ACT has a high water solubility (the solubility is 4200 mg L À1 in water at 293 K and pH ¼ 7) and is highly stable in the sun and in a weak acidic medium.…”
Section: Introductionmentioning
confidence: 99%